E-Bike Injuries: Experience from an Urban Emergency Department—A Retrospective Study from Switzerland - Sylvana Papoutsi; Luca Martinolli; Christian Tasso Braun; Aristomenis K. Exadaktylos (Emergency Medicine International)
Background. Between 2005 and 2012, annual sales of E-bikes in Switzerland increased from 1,792 to 52,941. This continuous and rapid transition from human-powered bicycles to an electric bicycle technology may indicate the increasing demand for low-cost transportation technology in combination with a healthy lifestyle. Material and Methods. In the present study, from April 2012 to September 2013, we retrospectively analysed E-bike accidents treated in the Emergency Department of our hospital by focusing on the following parameters: age, gender, time, period, and cause of the accident, as well as injury and outcome. Results. Patients were predominantly male. The mean age of injured E-cyclists was 47.5 years. The main causes of injury were self-accident. Most injuries were to the head/neck. The mean ISS was 8.48. The outcome showed that 9 patients were treated as outpatients, 9 were inpatients, and 5 patients were kept in the Intensive Care Unit (ICU). Only six patients underwent surgery (S). Discussion. This is the first attempt to evaluate E-bike injuries in Switzerland in an acute hospital setting. Since there is increasing popular preference for E-bikes as means of transportation and injuries to the head or neck are prevalent among E-cyclists, the hazard should not to be underestimated.